2018
DOI: 10.1177/1049909118809975
|View full text |Cite
|
Sign up to set email alerts
|

Palliative Care Consultation Trends Among Hospitalized Patients With Advanced Cancer in the United States, 2005 to 2014

Abstract: Background: Although palliative care services are increasing in the United States, disparities exist in access and utilization. Hence, we explored these factors in hospitalized patients with advanced cancers using the National Inpatient Sample (NIS). Methods: This was a retrospective analysis of NIS data, 2005 to 2014, and included patients 18 years with advanced cancers with and without palliative care consultations. Both w 2 and independent t tests were used for categorical and continuous variables. Multivar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
51
1
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(59 citation statements)
references
References 28 publications
5
51
1
2
Order By: Relevance
“…Rubens et al similarly found a correlation between both private insurance and high SES status and an increased utilization rate of PC. 20 These findings could be explained by the fact that private insurance plans provide access to additional PC intervention options compared to public plans, and that wealthier patients have greater capacity to afford out of pocket costs. 28,29 Disadvantaged socioeconomic groups tend to suffer greater symptom burden while experiencing terminal illness, suggesting that increased access to PC for all segments of our population is essential.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Rubens et al similarly found a correlation between both private insurance and high SES status and an increased utilization rate of PC. 20 These findings could be explained by the fact that private insurance plans provide access to additional PC intervention options compared to public plans, and that wealthier patients have greater capacity to afford out of pocket costs. 28,29 Disadvantaged socioeconomic groups tend to suffer greater symptom burden while experiencing terminal illness, suggesting that increased access to PC for all segments of our population is essential.…”
Section: Discussionmentioning
confidence: 99%
“…In investigating PC use disparities, we found that younger, lower SES, In our analysis, we found that patients older than the median age of 65 were more likely to receive PC than were younger patients; some previous studies have demonstrated a similar result. 20,21 Older patients may be more likely to have additional comorbid conditions existing with their advanced cancer that warrant more rigorous symptom management and goals of care discussions. This may explain the elevated PC utilization rate noted in this population.…”
Section: Discussionmentioning
confidence: 99%
“…Quanto à procedência dos artigos: 45,8% foram desenvolvidos em países da América do Norte 13,14,16,18,20,22,24,26,29,33,34 , 41,7% em países da Europa 15,17,21,23,25,[30][31][32]35,36 , 8,3% em países da América do Sul 27,28 e 4,2% em um país da Oceania 19 . Os países que mais publicaram sobre esta temática foram os Estados Unidos 13,14,16,18,20,22,24,26,29,33 , seguido por Portugal 17,21,25,32 e Bélgica 23,30,31,35 .…”
Section: Resultsunclassified
“…Despite the benefits of PC and growth of PC programs in the United States, the consultation rate for PC among hospitalized patients with advanced cancer is lower than 20%. 3 General insufficient public awareness, lack of access, and lack of social support may result in the underutilization of PC. 4 -8 As timely dissemination of evidence-based knowledge is an essential part in increasing the utilization of health care services, understanding the geographic disparity on perception of PC is rather important under the current promotion of PC programs across the United States.…”
Section: Introductionmentioning
confidence: 99%